EVALUASI PROGRAM TAHFIDZ DUA JUZ DI SD SEKOLAH ALAM YOUTH KHALIFA MENGGUNAKAN MODEL EVALUASI COUNTENANCE STAKE - Annisa Resya; Annisa Nurussobah; Radi Surya Nandana; Siti Nurul Kholillah; Dwi Arianto; Hesti Kusumaningrum (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to evaluate the Tahfidz Dua Juz Program at SD Sekolah Alam Youth Khalifa using the Countenance Stake Model, which assesses the antecedents, transactions, and outcomes of a program. Several implementation issues such as limited communication between teachers and parents, the absence of special strategies for students with special needs, unclear achievement indicators per grade level, and limited facilities serve as the background of this evaluation. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The analysis compares intended plans with observed practices and evaluates their alignment with program standards. The findings reveal that although the program is conceptually strong, its implementation faces obstacles that affect students’ memorization progress. The daily morning tahfidz routine runs effectively, yet parental involvement and differentiation for special-needs students remain suboptimal. Outcomes show that not all students achieve the two-juz target, prompting policy adjustments to a minimum of one juz. Overall, the program is running well but requires improvements in communication, facilities, and individualized learning strategies.